Penerapan Metode Certainty Factor Dalam Mendiagnosa Penyakit Kehamilan Berbasis Web - Dania Purnawan; Jhonson Efendi Hutagalung; Sri Rezki Maulina Azmi (Forum Kerjasama Pendidikan Tinggi, 2022)
Diseases or disorders in pregnancy can cause death, especially for pregnant women and babies. This will also affect the infant mortality rate. Diseases that attack a woman's womb cannot be considered trivial and require the intervention of an expert, while an expert for this disease is still rare and certainly requires no small cost. In creating experts (human experts), it takes a relatively long time and costs are not small. One alternative effort to overcome this need is to create a web-based intelligent system. In this study, an expert system will be developed that can be used as a means to carry out early diagnosis of pregnancy diseases. The application of the system is equipped with a certainty factor calculation method that aims to show the level of confidence in the diagnostic results. From the symptoms experienced there is a 20% certainty level and for toxoplasma there are 80% that the patient has gestational anemia.